Tailoring genetically altered Rice ASD 16 variety for enhanced stem girth through induced mutagenesis - Gowtham, K; Saravanan, S; Arumugachamy, S; Hepziba, S J; Rajinimala, N; Ravichandran, P; Allwin, L; Esakkimuthu, K (Plant Science Today, 2024)
In the rice variety ASD 16, induced mutation breeding was conducted using gamma irradiation and ethyl methanesulfonate (EMS) treatments, resulting in the generation of 850 M1 plants subjected to screening for key morphological and physiological traits. In the subsequent M2 generation, selected putative mutants were rigorously evaluated for their major morphological, anatomical and yield-contributing characteristics. This selection process identified 110 morphological mutants, 102 physiological mutants and 69 progenies exhibiting notably enhanced stem girth and superior yield potential. Genetic analyses conducted on the progenies of the M2 generation allowed for the isolation of superior putative mutants, revealing considerable genetic variability among them. Significant positive correlations were observed between productive tillers, stem girth and grain yield. Path analysis underscored productive tillers and stem girth as primary contributors to yield, while traits such as increased plant height and early flowering displayed a negative association with grain yield. Molecular characterization identified several mutants with robust culms and advantageous agronomic traits, supporting their potential for further breeding. Anatomical analysis showed marked differences in stem diameter, vascular bundle development, sclerenchyma cell density and starch accumulation among mutants, which were positively associated with enhanced mechanical strength and yield outcomes. Validation using molecular and genetic tools confirmed the superiority of the improved ASD 16 lines in yield and yield-contributing traits, offering valuable insights into the enhancement of rice crop resilience and productivity through induced mutagenesis.